Tantangan dan Implementasi Etika Profesi dalam Pengembangan Kecerdasan Buatan - Muhammad Rizcy; Evy Nurmiati (Journal of Literature Review, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought significant transformations across various sectors, yet it also raises complex ethical challenges. This article aims to analyze the main challenges and implementation strategies of professional ethics in AI development using the Systematic Literature Review (SLR) method. A total of 17 scientific articles published between 2023 and 2025 were analyzed to identify crucial issues. The review results indicate that the main challenges include algorithmic bias, model transparency (black-box), data privacy protection, and the social impact on the workforce. The implementation of ethics in Indonesia requires an integrative approach that combines local values (Pancasila), theological principles (Maqashid Al-Syari'ah), and formal legal frameworks (Personal Data Protection Law). These findings emphasize the importance of the system developer's role in maintaining moral accountability to ensure responsible AI development.